The impact of organisational capabilities on the performance of small- and medium-sized enterprises (SMEs) - Ofori-Amanfo, J.; Akonsi, S.W.; Agyapong, G.K. (European Business Review, 2022)
Purpose: The purpose of this study was to examine the extent to which organisational capabilities do impact the performance of small- and medium-sized enterprises (SMEs) in Ghana. Design/methodology/approach – A cross-sectional survey design was used for the study. Data was collected from 306 SMEs from different sectors of the economy. The partial least squares structural equation Modeling was used to analyse the relationships between organisational capabilities and SMEs’ performance measured by their financial viability. Findings: The findings reveal, as predicted, that four out of the five organisational capabilities tested were indeed important predictors of SMEs’ financial viability. Specifically, managerial capability, supply chain capability, operations capability and marketing capability were found to positively and significantly impact SMEs’ financial viability. The findings further reveal that firm size does not moderate the relationship between these capabilities and financial viability. Research limitations and implications: This study was undertaken in a developing economy with peculiar business operating conditions and, thus, may limit the generalisability of the findings. Practical implications: The findings suggest that key organisational capability development is critical for enhancing the financial viability of firms, confirming four of the critical capabilities that are needed by SMEs. The findings further suggest the need for firms, irrespective of size, to develop organisational capabilities. Originality/value: This study has empirically established that developing managerial capability, supply chain capability, operations capability and marketing capability are important success factors if SMEs. irrespective of size, intend to enhance their financial viability.
Research Article
Keywords: Organisational capabilities; Marketing capability; Managerial capability